2013
DOI: 10.2478/fobio-2013-0003
|View full text |Cite
|
Sign up to set email alerts
|

Citrullination – small change with a great consequence

Abstract: Citrullination is one of the possible post-translational modifications of proteins. It is based on a conversion of L-arginine residue (L-Arg) to L-citrulline residue (L-Cit). The reaction is catalyzed by peptidylarginine deiminases (PAD). The change of L-Arg imino moiety results in a loss of a positive charge. This slight modification can contribute to significant changes in physicochemical properties of proteins, which may also cause a change of their functions. Citrullination is the modification obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The citrullinated proteins are often found in the joints of RA patients but are not specific for the disease. In general, the citrullination of the protein may alter its tertiary structure, interaction with other molecules, cleavage regions, and its solubility to enhance its immunogenicity, which could stimulate the immune response to produce corresponding antibodies [21, 22]. It has been found that a large number of abnormally proliferating macrophages and lymphocytes infiltrate into the synovial tissue of RA patients.…”
Section: Acpamentioning
confidence: 99%
“…The citrullinated proteins are often found in the joints of RA patients but are not specific for the disease. In general, the citrullination of the protein may alter its tertiary structure, interaction with other molecules, cleavage regions, and its solubility to enhance its immunogenicity, which could stimulate the immune response to produce corresponding antibodies [21, 22]. It has been found that a large number of abnormally proliferating macrophages and lymphocytes infiltrate into the synovial tissue of RA patients.…”
Section: Acpamentioning
confidence: 99%